If it's not what You are looking for type in the equation solver your own equation and let us solve it.
92=4+6w+2w
We simplify the equation to the form, which is simple to understand
92=4+6w+2w
We move all terms containing w to the left and all other terms to the right.
-6w-2w=+4-92
We simplify left and right side of the equation.
-8w=-88
We divide both sides of the equation by -8 to get w.
w=11
| 7w+4w= | | 8p+(-6p)+6m= | | 6r+5t+4r= | | 8e+3(5+e)=10 | | 6x+8(2x+3)= | | 2x+3+3x+2=180 | | 5(x-6)+8=7x-10 | | 185-5x=31x+21 | | 2k+5=12 | | 0=(-(x+4)(x+4))-7 | | 40+14y=-20-8y-6 | | 7z+4=-5z-2 | | -12=3(2n-10) | | 5y-3x+2y-4x= | | 4x-6=-31 | | -3y+2x= | | 7x+-12=2 | | 30x-25=50-20x | | -8d-(-2d)-6d= | | 16-x+2=23 | | 15b-24b= | | 888x=111 | | 7t+4t= | | N=zx-d | | 6rs+5r+8s-rs-r-s= | | 6-5j=-94 | | -0.5x+10=1.5x-5 | | -(5x+12)=12 | | -j+4k+jk-5jk+5j= | | 12x^2+5x-2x=0 | | .83+3j=-.67 | | 10y-4y= |